CORPORATE ENVIRONMENT OF HIGHER SCHOOL: ANALYSIS OF TERM - Viktoria V. Levchenko; Alexandr V. Levchenko; Elena A. Sokolova (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
It is analyzed the main scientific points of view on intentional structure of corporate environ-ment in this article. It is definited the structural composition of university corporate environ-ment and correlation of its components in our work. Sorting out of targeted, technological, sociocultural, motivational, reflexive components in the structure of university corporate environment carried out with the help of management processes. It is proved the mutually determinacy of the components with the main management functions (planning, coordination, organizing, motivation, control).